2023
DOI: 10.1111/jcpp.13871
|View full text |Cite
|
Sign up to set email alerts
|

Early childhood general anesthesia and risk of Attention Deficit Hyperactivity Disorder

Abstract: BackgroundThe relationship between early childhood exposure to general anesthesia (GA) and the risk of developing Attention Deficit Hyperactivity Disorder (ADHD) is still uncertain and previous studies have presented conflicting results. This population‐based cohort study aimed to investigate the potential relationship between GA exposure and ADHD risk using propensity score matching (PSM) in a large sample size.MethodsThe study included 15,072 children aged 0–3 years who received GA and were hospitalized for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Attentional de cits and hyperactivity disorders tend to be more prevalent in male than in female children [42], whereas female sex is an established risk factor for anxiety disorders [43]. A clinical study has also shown that male sex is signi cantly associated with ADHD [7]. These ndings are consistent with our study ndings in the subgroup analyses of sex.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Attentional de cits and hyperactivity disorders tend to be more prevalent in male than in female children [42], whereas female sex is an established risk factor for anxiety disorders [43]. A clinical study has also shown that male sex is signi cantly associated with ADHD [7]. These ndings are consistent with our study ndings in the subgroup analyses of sex.…”
Section: Discussionsupporting
confidence: 91%
“…The ndings of our study also suggested that prolonged anesthesia (≥ 3 hours) was associated with an increased risk of ADHD. In another study, the aHRs of ADHD in children who underwent general anesthesia for less than 3 hours or 3 hours or more were 1.20 (95% CI: 1.07, 1.99) and 1.89 (95% CI: 1.48, 2.16), respectively, compared to those who did not receive general anesthesia [7]. In our study, we also found that the dimension of impulsivity-hyperactivity differed signi cantly between prolonged-exposure children and unexposed children, but there was no statistically signi cant difference between children exposed for less than 3 hours and unexposed children.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations